(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2004)
We present quantitative data on calcareous nannofossil biostratigraphy in the section of Montalbano Jonico (Southern Italy). This is one of the candidate Global Statotype Section and Point (GSSP) of the Middle Pleistocene. The first common occurrence (FCO) and last common occurrence (LCO) of Reticulofenestra asanoi are well detectable in the section and are here proposed as additional events for improving biostratigraphic resolution in the interval corresponding to the transition between the small Gephyrocapsa Zone and Pseudoemiliania lacunosa Zone. The potential value of the bioevents is tested in a Mediterranean deep-sea core of ODP Site 964, located in the Ionian Sea. At Site 964 the FCO of R. asanoi occurs in the marine oxygen isotope stage (MIS) 30, and the LCO of the species correlates with MIS 23. The ages of the FCO and LCO of R. asanoi have been estimated at 1.06 Ma and 0.93 Ma respectively. The first occurrence (FO) of Gephyrocapsa sp. 3 has been correlated to MIS 25, both at Site 964 and at the Montalbano Jonico section. The age of the FO of Gephyrocapsa sp. 3 is estimated at 0.95 Ma, based on the astronomical datings of sapropels occurring at the Montalbano Jonico section. In addition, an interval of temporary disappearance of Gephyrocapsa sp. 3 has been identified within the P. lacunosa Zone. The beginning of this interval is correlated with MIS 20/19 and can be considered a reliable event in the Mediterranean area, occurring close to the Brunhes/Matuyama magnetic boundary. The recognized events provide a basis for interpreting the Montalbano Jonico section within a standard chronostratigraphic framework.